Using Content, Context, and Process to Manage University Cutbacks - Hardy, Cynthia (Canadian Journal of Higher Education, 1987)
Funding and enrolment problems have led to recommendations for more strategic planning in universities. The traditional model of strategy making may not be appropriate, however, because it focuses on the content of strategies and ignores other elements in the strategy making process. Universities are very much constrained in terms of their choice of retrenchment strategy - they cannot fire tenured staff or close faculties in the way a business can shut down factories and lay off employees. A second problem is that the traditional model defines success purely in economic terms whereas universities can be effective only if they maintain morale and commitment. Thus, success involves a political component. Two Canadian universities faced with retrenchment are compared to show that, while the same cutback mechanisms were used, the process of implementing them was quite different. The result was similar economic outcomes but great variation in political terms. The article argues that the key to success is matching the content of the strategy with a process of implementation that is consistent with the particular university context. Thus, successful retrenchment strategy making may look different in different institutions.